ZnO-PLLA Nanofiber Nanocomposite for Continuous Flow Mode Purification of Water from Cr(VI). (23rd November 2015) - Burks, T.; Akthar, F.; Saleemi, M.; Avila, M.; Kiros, Y.
Abstract : Nanomaterials of ZnO-PLLA nanofibers have been used for the adsorption of Cr(VI) as a prime step for the purification of water. The fabrication and application of the flexible ZnO-PLLA nanofiber nanocomposite as functional materials in this well-developed architecture have been achieved by growing ZnO nanorod arrays by chemical bath deposition on synthesized electrospun poly-L-lactide nanofibers. The nanocomposite material has been tested for the removal and regeneration of Cr(IV) in aqueous solution under a "continuous flow mode" by studying the effects of pH, contact time, and desorption steps. The adsorption of Cr(VI) species in solution was greatly dependent upon pH. SEM micrographs confirmed the successful fabrication of the ZnO-PLLA nanofiber nanocomposite. The adsorption and desorption of Cr(VI) species were more likely due to the electrostatic interaction between ZnO and Cr(VI) ions as a function of pH. The adsorption and desorption experiments utilizing the ZnO-PLLA nanofiber nanocomposite have appeared to be an effective nanocomposite in the removal and regeneration of Cr(VI) species.